Replaced right hepatic artery associated with uncommon triplet right renal vein: embryological perspective and clinical importance - Satheesha, NB; Srinivasa, RS; Surekha, DS; Naveen, K; Anita, G (Department of Surgery, UKM Medical Centre, 2012)
Vascular variations in the abdomen are common and mostly asymptomatic. Knowledge of these variations are of tremendous clinical importance in patients undergoing invasive endovascular interventions such as liver transplantation, renal transplantation, and vascular reconstruction for congenital and acquired lesions and trans-arterial chemoembolization for the hepatic tumors. During regular dissection classes for the medical undergraduates, we encountered concurrent vascular variations in an elderly male cadaver. In the present case, we report multiple vascular anomalies involving the right hepatic artery and the right renal vein. The right hepatic artery branched off from superior mesenteric artery, and it was identified as a replaced right hepatic artery. The right kidney was drained by three renal veins, the uppermost among the three twisted around the superior branch of the right renal artery before terminating into the inferior vena cava. In addition, the left kidney was supplied by two renal arteries, and drained by a single renal vein.